2019
DOI: 10.1002/dmrr.3140
|View full text |Cite
|
Sign up to set email alerts
|

Gall bladder: The metabolic orchestrator

Abstract: It is commonly held that the gall bladder (GB) is not indispensable for life. However, recent studies strongly suggest that GB removal can lead to the development of metabolic syndrome (MetS). With the recent recognition of the role of bile acids (BAs) in systemic metabolic regulation, it is worthwhile to re-examine the function of the GB, which can be regarded as the physiological "pacemaker" of BA flow. Thus, in the present study, we review the role of the GB in BA flow regulation, describe the epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…The possibility of correlation between cholecystectomy and LF or LC is further supported by the findings from the present study. After cholecystectomy, changes in bile flow and concentration of bile acid in the bile duct ( 33 ) might occur, which may cause chronic cholestasis, NAFLD and metabolic syndrome ( 10 , 34 36 ). Interestingly, the study showed that participants with cholecystectomy for over 14 years had a higher incidence of LF than those <14 years ( Supplementary Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of correlation between cholecystectomy and LF or LC is further supported by the findings from the present study. After cholecystectomy, changes in bile flow and concentration of bile acid in the bile duct ( 33 ) might occur, which may cause chronic cholestasis, NAFLD and metabolic syndrome ( 10 , 34 36 ). Interestingly, the study showed that participants with cholecystectomy for over 14 years had a higher incidence of LF than those <14 years ( Supplementary Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy is among the most common operations performed worldwide, with 750,000–1,000,000 procedures conducted in the United States, annually ( 42 ). Considering the early and delayed complications associated with cholecystectomy, it would be important to reassess the function and importance of the gallbladder ( 34 ). Strict surgical indications should also be implemented to reduce unnecessary cholecystectomy ( 43 ), given that preoperative evaluation of abdominal pain through gastroduodenoscopy was reported to be able to prevent 3.8% of cholecystectomies ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another cause suggested that excessive amounts of bile acids in the colonic lumen could be irritating and toxic to the colonic epithelium [ 51 ]. Bile acid synthesis has a sharp rise after meals, and the peak occurs from 09:00 to 10:00 p.m. [ 52 ]. Hence, a higher calcium intake at dinner may be more likely to induce the conversion of bile acids to insoluble calcium compounds, thereby reducing the adverse effect of bile acids on the colonic epithelium and decreasing the incidence of gastrointestinal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Another cause suggested that excessive amounts of bile acids in the colonic lumen could be irritating and toxic to the colonic epithelium [30]. The bile acid synthesis has a sharp rise after meals, and the peak occurs at 09:00 to 10:00 p.m. [31]. Hence, higher calcium intake at dinner may be more likely to induce the conversion of bile acids to insoluble calcium compounds, thereby reducing the adverse effect of bile acids on the colonic epithelium and decreasing the incidence of gastrointestinal tumors.…”
Section: Discussionmentioning
confidence: 99%